2022
DOI: 10.1126/sciadv.abo2829
|View full text |Cite
|
Sign up to set email alerts
|

Viral shunt in tropical oligotrophic ocean

Abstract: Viruses cause massive bacterial mortality and thus modulate bacteria-governed carbon transfer and nutrient recycling at global scale. The viral shunt hypothesis states the crucial role of viral lysis in retaining microbial carbon into food web processes, while its applicability to nature has not been well identified for over two decades. Here, we conducted nine diel surveys in the tropical South China Sea and suggested that the time scale adopted in sampling and system trophic status determine the “visibility”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Thus, higher microbial abundances (VA and BA) and production (BP) were observed at S1, compared with those at S2 and S3 (Figures 3 and 5). VA, BA and BP in our study were comparable to the previous reports in the study area (Shiah et al., 2022; Xu et al., 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, higher microbial abundances (VA and BA) and production (BP) were observed at S1, compared with those at S2 and S3 (Figures 3 and 5). VA, BA and BP in our study were comparable to the previous reports in the study area (Shiah et al., 2022; Xu et al., 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The river discharge delivered nutrients and triggered phytoplankton growth in the nearshore waters (e.g., S1) (Xu et al., 2018), potentially enhancing the supply of phytoplankton‐derived and high‐molecular‐weight DOC (Kirchman, 2002), which bacteria preferentially utilize (Shi et al., 2019; Xu et al., 2018). The offshore station S2 and S3 located at substrate‐low SCS, where low molecular weight DOC and less bioavailable bacteria and virus‐derived DOC were likely dominated (Dong et al., 2013; Shiah et al., 2022). It is reported that a majority of high molecular‐weight DOC is relatively bioavailable to heterotrophic bacteria, while low molecular‐weight DOC is utilized at a higher energy cost (Benner & Amon, 2015; Stocker, 2012).…”
Section: Discussionmentioning
confidence: 99%